Sodium-glucose Cotransporter-2 Inhibitors as Modulator of Dipeptidyl Peptidase-4 in Diabetes - Rafeeq, Misbahuddin M.; Haque, Shahnaz; Sain, Ziaullah M.; Alzamami, Ahmad; Alturki, Norah A.; Mashraqi, Mutaib M.; Alghamdi, Youssef Saeed; Alniwaider, Rashed Ahmed; Patel, Ayyub (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Genetic disorders such as diabetes have severe implications on human health. Mutation or aberrant activity of different proteins are associated with diabetes. The hyperactivation of the peptidase function of dipeptidyl peptidase-4 (DPP4) strongly correlates with the elevated level of blood glucose in diabetic patients. Aim: Preventing the activity of DPP4 by small molecule modulators is an excellent approach that proposes to curb the aggressiveness of diabetes. Blocking the DPP4 function quantitatively raises glucagon-like peptide 1 (GLP-1) in the blood that finally lowers the level of glucose in circulating fluids. Materials and Methods: In this study, we have conducted an elaborate investigations of the sequence-based structural properties of DPP4 protein by using various computational methods in order to find protein’s antigenic and drug-binding regions. Results: Using the dataset of sodium-glucose transport protein 2 (SGLT2) inhibitors, we have identified a set of molecules that are predicted to bind DPP4. We have characterized the dipeptide ubenimex as the most potential modulator of DPP4. Conclusion: Based on the findings of current study, we concluded that our study has decoded the inhibitory module of DPP4 by the approach of structure-guided drug identification.
Keywords: SGLT2; DPP4; Docking; Diabetes; Ubenimex